Answers

2016-04-24T19:58:31+05:30
= 2 y^{2} + 7y +5


We know that : 
          \alpha + \beta =  \frac{-b}{a}  \\ \\   \alpha + \beta = \frac{-7}{2}
Further:
           \alpha  \beta  = \frac{c}{a} \\  \\  \alpha  \beta = \frac{5}{2}

Now, we need:
           \alpha ^{2} +  \beta ^{2} = ( \alpha + \beta )^{2} -2 \alpha  \beta  \\  \\  \alpha ^{2} +  \beta ^{2} = ( \frac{-7}{2}) ^{2} - 2( \frac{5}{2}) \\  \\    \alpha ^{2}  +  \beta ^{2}=  \frac{49}{4}-5 \\  \\   \alpha ^{2}  + \beta ^{2}= \frac{49-20}{4}  \\  \\  \alpha^{2}+ \beta  ^{2}  =  \frac{29}{4}
0